Randomised clinical trial: l‐ornithine‐l‐aspartate reduces significantly the increase of venous ammonia concentration after TIPSS. Issue 1 (15th May 2014) - Bai, M.; He, C.; Yin, Z.; Niu, J.; Wang, Z.; Qi, X.; Liu, L.; Yang, Z.; Guo, W.; Tie, J.; Bai, W.; Xia, J.; et al.
Summary Background Use of TIPSS is associated with increases in ammonia concentration and hepatic encephalopathy (HE) risk. l‐ornithine‐l‐aspartate (LOLA) is effective in reducing ammonia concentration. Aim To evaluate the effects of LOLA on venous ammonia concentration after TIPSS. Methods The included patients were randomised to receive LOLA or no‐LOLA treatment for 7 days. Fasting and post‐prandial venous ammonia levels were the primary outcomes. Psychometric performance, post‐TIPSS HE, and liver and renal function were assessed as secondary outcomes. Results Of 133 cirrhotic patients who received successful TIPSS between November 2011 and June 2012, 40 met the inclusion criteria and were randomised to the LOLA (n = 21) or control (n = 19) groups. Change in fasting ammonia significantly favoured the LOLA group at days 4 (P = 0.001) and 7 (P = 0.003). Changes in post‐prandial ammonia concentration significantly favoured the LOLA group at days 1, 4 and 7 as well. During the study period, patients in the LOLA group had better improvement in psychometric tests than those in the control group. Overt HE during treatment was observed in one patient in the LOLA group and three patients in the control group (P = 0.331). There were no differences in complications, adverse events or mortality between the two groups. Conclusions Prophylactic use of LOLA infusion after TIPSS is safe and effective in significantly reducing the increase of venous ammonia concentration, and can benefit the patient's mental status as well.